COACHING AS PHILOSOPHY AND TECHNOLOGY OF DEVELOPMENT PROFESSIONAL PEDAGOGICAL EDUCATION - Savchuk, Borys; Bilavych, Halyna; Dushenko, Yulia (Mountain School of Ukrainian Carpaty, 2019)
The article deals with a structured researches of ideological principles and methods and techniques of coaching in the context of their loyal and effective use in the organization of educational process of the pedagogical university and vocational training of future teachers. The etymology of the concept «coaching» its variants and features of educational coaching. In the context of higher education development and improvement of professional pedagogical education, coaching has been considered and characterized in four interrelated aspects: 1) the subject-subject dialogue paradigms in the studentteacher dyad (conscious principles of partnership, conscious awareness), hierarchy of development, flexibility, holism); 2) coaching competence as a component of professional competence; 3) coaching technology (GROW, SMART techniques and techniques, soft skills; three dimensions – 3D, etc.); 4) portfolio of achievements. Coaching as a kind of multidisciplinary multidimensional philosophy and technology of personality formation and development has proven effective in various areas of public life. Аpplying of coaching as a factor and tool for the development of higher education and improvement of professional pedagogical education is manifested in interrelated aspects concerning the paradigm of subject-subject dialog relations in the student-teacher dyad, formation of participants in the educational process of coaching, applying of coaching methods and techniques for the personal and professional growth of the educational acquirer and the portfolio of achievements for the reflection and self-reflection of successes and failures in the path of self-development. Therefore, coaching philosophy and technology have significant potential in forming a competent and competitive educator.